The establishment & implementation of the supplier agreement management(SAM) process area for procurement unit at Heitech Padu Berhad (HTP) - Abdulgabber, Mansoor Abdullateef; Mohd Naz'ri Mahrin.; Fakulti Sains Komputer dan Sistem Maklumat (2006)
Thesis (Sarjana (Sains Komputer)) - Universiti Teknologi Malaysia, 2006